Social Capital of Pancasila Education in Smart Education with Social Media in Cybercrime Prevention in the Industrial Revolution Era 4.0 - Wen Akhuai; Aloisius Arizendy Nugraha; Yosephine Ken Rahayu Dyah Lukitaningtyas; Aly Ridho; Heni Wulansari; Risang Adhitya Al Romadhona (Universitas Negeri Semarang, 2022)
Currently the world is undergoing major changes, namely the Industrial Revolution 4.0. The Industrial Revolution 4.0 is a change in the mechanism for the production of goods and services marked by a number of characteristics, namely the use of the internet of things, big data, automation, robotics, lay computing, to artificial intelligence. This change is not only felt by the private sector, but also by government organizations. What the community, especially students, can do to play a role in this industrial era and take steps and places as the driving force of this country is to develop a critical thinking pattern that is not easily eroded by negative influences. This means that with the amount of information that can be obtained, students must be able to see which information can be trusted and which is not and do not immediately believe in any information that is not necessarily true. In addition to the various opportunities offered in the Industrial Revolution 4.0 era, there are many new public issues that must be faced, such as online transportation polemics, the threat of e-commerce to conventional shops/retails and cybercrime. This time, we focus on cybercrime. Cybercrime is a crime that is carried out electronically. This crime takes various forms. The presence of Law Number 11 of 2008 concerning Electronic Information and Transactions has regulated the prohibited actions related to electronic information and transactions. The problem of violence that occurs through online media in fact poses a problem for the whole community. For this reason, everyone needs to get a good understanding of the impact of cybercrime, and the potential emergence of women as victims of these crimes, such as cyberstalking and cyberpornography. Through this education, it is hoped that the community will understand their rights to the maximum, especially those related to the right to obtain education and the freedom to express their opinions.